Faktor Meningkatkan Literasi Sains pada Mahasiswa Calon Guru SD/MI - Hutasuhut, Riska fadhilah; Faridah, Eva; Surya, Edy (Al-Azkiya: Jurnal Pendidikan MI/SD, 2025)
This research aims to identify and map the results of previous research on factors that can increase scientific literacy for prospective elementary school or Madrasah Ibtidaiah (MI) teacher students using a meta-analysis study. Journals were obtained using AI elicitation and consensus. Scientific literacy must be instilled in prospective teacher students, because scientific literacy is a 21st century requirement that must be possessed by students, especially elementary school students. Previous research results showed that the scientific literacy of Elementary School Teacher Education (PGSD) or Madrasah Ibtidaiyah (MI) Teacher Education students was still low. The integration of instilling scientific literacy values ​​in science learning in elementary schools is expected to increase the scientific literacy of students in Indonesia. These factors can be improved in various ways, such as using scientific learning models, learning media, ethnoscience-based learning, and improving science concepts in science learning at school.